Analysing Lexico-grammatical Features in Chimamanda Ngozie Adichie’s Americanah - LOKO, Djima Crépin; KOUTCHADE, INNOCENT SOUROU (My University, 2016)
This article aims at carrying out an analysis of Chimamanda Ngozi Adichie’s Americanah (2013), using the Systemic Functional Linguistics (SFL). Such a linguistic approach views language as a strategic meaning-making resource (Halliday & Matthiessen, 2004; Eggins, 1994). The main and specific goal of the present study is to describe and analyse the lexico-grammatical features, characteristics of the language of Adichie’s Americanah. This leads to focus on the study of linguistic patterns such as Transitivity, Mood and Theme in three selectedexcerpts from the novel. The socio-cultural context of the production of the novel has made it easy to discuss and interpret the salient linguistic patterns which reveal the generic structure potential of the novel and has facilitated the study of how the novelist has woven her text as a message of alert through the depiction of such issues as immigration, love, race and identity in the context of today’s globalised world.
Keywords: Systemic Functional Linguistics (SFL); Chimamanda Ngozi Adichie; Transitivity; Mood; Theme